2022
DOI: 10.3390/catal12101231
|View full text |Cite
|
Sign up to set email alerts
|

Direct One-Step Seedless Hydrothermal Growth of ZnO Nanostructures on Zinc: Primary Study for Photocatalytic Roof Development for Rainwater Purification

Abstract: To shift towards the greener city, photocatalytic urban infrastructures have emerged as a promising solution for pollution remediation. To reach this goal, the large bandgap semiconductors, such as nontoxic Zinc Oxide (ZnO), already proved their excellent photocatalytic performances. However, integrating and developing cost-effective and greener photocatalytic surfaces with an easily scaled-up synthesis method and without energy and chemical product overconsumption is still challenging. Therefore, this work pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…The calculated band gap is 3.75, 3.80, and 3.70 eV for ZnO-1, ZnO-2, and ZnO-3, respectively. These values are quite higher as compared to previously published work that shows the ZnO bandgap around 3.0-3.4 eV [5,28,40]. Here, a lower pH solution (ZnO-2) has a higher band gap, while the higher pH (ZnO-3) shows otherwise.…”
Section: Optical Propertiescontrasting
confidence: 63%
See 1 more Smart Citation
“…The calculated band gap is 3.75, 3.80, and 3.70 eV for ZnO-1, ZnO-2, and ZnO-3, respectively. These values are quite higher as compared to previously published work that shows the ZnO bandgap around 3.0-3.4 eV [5,28,40]. Here, a lower pH solution (ZnO-2) has a higher band gap, while the higher pH (ZnO-3) shows otherwise.…”
Section: Optical Propertiescontrasting
confidence: 63%
“…Among the various renewable energy sources, solar energy is a viable option to address the abovementioned problems independently. A previous study showed that rooftops have the potential to be used as a large photocatalytic reactor, using sunlight for rainwater purification [5]. A semiconductor photocatalyst is one of the most suitable for green energy production because it is relatively cheap and easy to implement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in [12], the authors use a photocatalysis method for rainwater purification, where they develop a decontaminating zinc (Zn) roof covered by ZnO nanostructures (NS) using a one-step seedless hydrothermal growth method in 2 h.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ZnO nanomaterials has been booming since the 1990s [1][2][3][4][5][6]. Due to its excellent characteristics, zinc oxide has always maintained a high degree of attention in the fields of energy, environment, biology, and detection [7][8][9][10][11][12][13]. In these decades of research, controllable growth and cost reduction are two aspects to which people have been committed.…”
Section: Introductionmentioning
confidence: 99%